Implementation Of Hydrotherapy as a Potential Community Service Activity in Bantengan Arts in Malang Regency, East Java - Donny Setiawan; Wawan Setiawan; Galih Farhanto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The Bantengan art form involves physical movements that can cause fatigue in the performers, particularly in the legs. Long-term practice and performance activities can lead to fatigue. Fatigue can interfere with daily activities and performance. This article aims to describe the implementation of hydrotherapy as a potential community service activity in the Bantengan art form in Malang, East Java. The article was compiled through observations and interviews with the Putra Mandala Junior (PMJ) art group, whose members are children aged 9–14 who are still attending elementary and middle school. The fatigue experienced has the potential to disrupt learning activities at school, thus impacting academic achievement. The results of the observations and interviews serve as the basis for developing potential hydrotherapy applications. The implementation concept is presented in the form of problems and solutions, activity methods, and applicable hydrotherapy technologies. Hydrotherapy technology is presented in schematic form with explanations to form the basis for technological application.